Efeito de Bacillus subtilis aplicado em pré ou pós-plantio no controle da meloidoginose e sobre alterações fisiológicas no tomateiro - Bavaresco, Lorrayne Guimarães (2018)
Among the forms of biological control, the use of rhizobacteria has shown to be promising in the suppression and protection of plants against the attack of phytonematoids. The objective of this work was to evaluate the effect of Bacillus subtilis on the reproduction of Meloidogyne spp., associated to changes in rhizosphere colonization and growth, nutrition and enzymatic activity of tomato cultivars tolerant and susceptible to root-knot nematodes. The methods of application consisted of the inoculation of Bacillus subtilis (AP-3) in pre-planting and post-planting of the tomato. Two experiments were conducted in a plant growth chamber. In the first experiment the tomato plants were cultivated on a sterile substrate, inoculating 5000 eggs of Meloidogyne incognita. In the second, tomato cultivation was carried out in sandy soil naturally infested with root-knot nematodes. The plant growth, nematode reproduction, soil and rhizosphere colonization by bacteria of the genus Bacillus spp., and biochemical changes were evaluated at 40 days after transplanting of the tomato. In both modes of application, the Bacillus subtilis was efficient in increasing root mass and in reducing the reproduction of the root-knot nematode in susceptible tomato cultivated in naturally infested soil. In sterile substrate, inoculation of B. subtilis in post-planting promoted reduction of the number of active forms of the nematode and both applications promoted the decrease of eggs of Meloidogyne incognita in the roots of the tomato. The application of B. subtilis, as a sterile substrate, induced changes in the nutritional uptake of tomato plants, increasing calcium levels and reducing leaf potassium. The application of B. subtilis contributed to the reduction of the peroxidase activity in leaves of the tomato susceptible to root-knot nematodes, in sterile condition. The rhizobacteria, after planting, allowed the increase in the proline content in the leaves of the tomato, cultivated in soil naturally infested with root-knot nematodes. Inoculations with B. subtilis promoted an increase in the number of Bacillus spp. in the sterile substratum and in the rhizosphere of the tomato, being confirmed the persistence of these bacteria at 40 DAP.